2016
DOI: 10.1101/089961
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome sequencing and analysis of the first spontaneous Nanosilver resistant bacteriumProteus mirabilisstrain SCDR1

Abstract: 33Background: P. mirabilis is a common uropathogenic bacterium that can cause major complications in 34

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Previous reports on antimicrobial susceptibility tests on P. mirabilis strains have reported that P. mirabilis strains are naturally susceptible to Rifamycin and Fusidic acid (Armbruster et al, 2018). But due to the presence of AMR genes, P. mirabilis has acquired the resistance against these antibiotics (Saeb, Al‐Rubeaan, Abouelhoda, Selvaraju, & Tayeb, 2017; Sohail, Khurshid, Murtaza Saleem, Javed, & Khan, 2015). We analyzed the drug resistance patterns of each P. mirabilis strain included in our study using ResFinder.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports on antimicrobial susceptibility tests on P. mirabilis strains have reported that P. mirabilis strains are naturally susceptible to Rifamycin and Fusidic acid (Armbruster et al, 2018). But due to the presence of AMR genes, P. mirabilis has acquired the resistance against these antibiotics (Saeb, Al‐Rubeaan, Abouelhoda, Selvaraju, & Tayeb, 2017; Sohail, Khurshid, Murtaza Saleem, Javed, & Khan, 2015). We analyzed the drug resistance patterns of each P. mirabilis strain included in our study using ResFinder.…”
Section: Resultsmentioning
confidence: 99%
“…This enhanced resistance to antimicrobial agents has resulted not only in modifications to antimicrobial therapies, but also in poor diagnosis and increased mortality rate of nosocomial infections [28]. Astonishingly, in 2016, a new isolate of P. mirabilis, from diabetic ulcer patient, have shown a remarkable resistance to silver nanoparticles, spreading the alarm of resistance to even include metallic nanoparticles like silver [29]. Moreover, the efflux pumps (EPs) also play important role in P. mirabilis drug resistance, as exemplified of the increased cell permeability of the EP inhibitor Phenylalanine-Arginine Beta-Naphthylamide (PAβN), thereby making it more susceptible to acetylsalicylic acid [30].…”
Section: Proteus Mirabilismentioning
confidence: 99%
“…On the other hand, Proteus spp. genome carries antibiotic resistance loci towards different mechanisms of antimicrobial agents and metals, including swarming mobility, biofilm formation, enzymatic detoxification and efflux systems by employing the PATRIC and PGAAP gene explanation services [75][76][77].…”
Section: Determination Of Antibacterial Activity and Micmentioning
confidence: 99%